2023
DOI: 10.3390/rs15174349
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Based Hyperspectral Retrieval of Soil Arsenic Concentration in Pingtan Island, China

Meiduan Zheng,
Haijun Luan,
Guangsheng Liu
et al.

Abstract: The optimal selection of characteristic bands and retrieval models for the hyperspectral retrieval of soil heavy metal concentrations poses a significant challenge. Additionally, satellite-based hyperspectral retrieval encounters several issues, including atmospheric effects, limitations in temporal and radiometric resolution, and data acquisition, among others. Given this, the retrieval performance of the soil arsenic (As) concentration in Pingtan Island, the largest island in Fujian Province and the fifth la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…However, these global models assume that the relationship between the dependent and independent variables is the same in different subregions. This assumption may lead to the poor fitting performance of these models in areas with strong landscape heterogeneity [ 10 , 17 ]. Moreover, the global regression model can only reveal the average relationship between As and covariates throughout the entire study area and thus cannot provide data support for local As pollution treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these global models assume that the relationship between the dependent and independent variables is the same in different subregions. This assumption may lead to the poor fitting performance of these models in areas with strong landscape heterogeneity [ 10 , 17 ]. Moreover, the global regression model can only reveal the average relationship between As and covariates throughout the entire study area and thus cannot provide data support for local As pollution treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exploring the main sources and influencing factors of soil As is crucial for reducing soil arsenic pollution, protecting soil ecology, and ensuring human health. The Kriging model [8], principal component analysis/cluster analysis [9], multiple linear regression (MLR) [10], geographical detectors [11,12], spatial lag models [13], and machine learning methods [14][15][16] have been used to explore the main influencing factors of As. These studies revealed that the main sources of As include mineral mining, industrial smelting, agricultural production, fossil energy combustion, traffic emissions, and some As-rich minerals (e.g., hutchinsonite and arsenopyrite).…”
Section: Introductionmentioning
confidence: 99%